HALAL ṬAYYIB SYARIA’ IN UNDERSTANDING THE NEEDS OF CONSUMER PROTECTION - Nur Aksin; Fiki Nu‘afi Qurrota Aini (fakultas hukum universitas PGRI Semarang, 2023)
Concept of halal ṭayyib always can follow time progress and lifestyle of people from time to time. Although the concept of halal ṭayyib born of a religion (Islam), but that is not restricted to among that is required by law (syari‘at) but also to all mankind. When viewed from the definitions, halal ṭayyib is a whole body and cannot be separated. However, the fact is that not all halal things will have a ṭayyib values in it. Instead, if a thing has been ṭayyib values, then of course it is a Halal. It is influenced by several factors that cause has no tayyib values in it, so cannot be categorized as a good things. For that reason, the whole concept halal tayyib really need to further review, as will be presented in this research. The concept of halal tayyib will review deeply using qualitative research studies as well as several references to the research pertaining to the concept of halal tayyib thoroughly.This research included in the qualitative study based on research literature (library research), which use descriptive data dissemination and use mode of semiotic analysis method which is content analysis, where this research attempts to develop the information and used to deepen and enlarge existing knowledge. This research use the sociological approach, where used to know and understand social trend pertaining to the existence of the concept of halal ṭayyib and how to solving the problem. The primary data from Indonesian Ulama’s instructions about the halal terms of a product and Qur’an Hadiṡ as the main source of halal ṭayyib law. As for secondary data used are a few other literature which relate to halal ṭayyib terms, just like some journals and research about halal ṭayyib, some government regulations, and all the other several references that deals with this research.